Antibacterial activity of mexican sunflower leaf Tithonia diversifolia (Hemsl.) A.Gray Aqueous extract against methicillin-resistant Staphylococcus aureus - Misrahanum Misrahanum; Zahratul Safarah; Yulia Sari Ismail (Pharmaciana, 2022)
The research of antibacterial activity of Mexican sunflower leaf Tithonia diversifolia (Hemsl.) A.Gray aqueous extract against Methicillin-Resistant Staphylococcus aureus (MRSA) was carried out. The research aimed to observe the antibacterial activity of Mexican sunflower leaves aqueous extract to inhibit the growth of MRSA with concentrations of 10, 20, 30, 40, and 50%. The extracts were obtained by the maceration method, and the antibacterial activity was tested using the agar well diffusion method. Characterization of Mexican sunflower leaves simplicia were obtained with water level 9%, water-soluble level 21,6%, ethanol-soluble level 10,3%, and total ash level 14,36%. Characterization of Mexican sunflower leaves aqueous extracts were obtained with water level 26,36%, water-soluble level 53,13%, ethanol-soluble level 26,36%, and total ash level 19,98%. Phytochemical screening revealed that aqueous extract of Mexican sunflower leaves contained secondary metabolites of alkaloids, flavonoids, tannins, and saponins. The largest inhibitory zone was shown at a 50% extract concentration with a diameter of 12,40 mm. The aqueous extract of Mexican sunflower leaves was capable to form the inhibition zone on the MRSA growth.